Bondsvoorzitter van der Meijs van de R.k. textielarbeiders spreekt 7000 arbeiders toe. Uit De Katholieke Illustratie
Bondsvoorzitter van der Meijs van de R.k. textielarbeiders spreekt 7000 arbeiders toe. Uit De Katholieke Illustratie.